Reign of fire [videorecording (DVD)] - Bowman, Rob; Bale, Christian, 1974-; Scorupco, Izabella; Butler, Gerard, 1969- (Touchstone Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2002)
In present day London dragons awake. Fast forward 20 years, to a world devastated by their destruction. Fire Chief Quinn is responsible for warding off the beasts and keeping a community alive in what's left of the world. Into their midst comes a hotshot American, Van Zan, who says he has a way to destroy the beasts and save mankind.